Lung cancer screening with low-dose computed tomography: National expenditures and cost-effectiveness - Zeng, Xiaohui; Zhou, Zhen; Luo, Xia; Liu, Qiao (Frontiers in Public Health, 2022)
Objective To compare the cost-effectiveness of different frequencies of undertaking low-dose computed tomography (LDCT) screening for early detection of lung cancer (LC) within the healthcare system of China, and estimate the additional national healthcare expenditure and five-year LC mortality associated with each screening frequency. Material and Methods A Markov model was built using national LC epidemiological data from the Chinese Center for Disease Control and Prevention, demographic data from the Chinese Statistical Yearbook, and cost and effectiveness data mainly from the Cancer Screening Program in China. The models included thirty sex-specificity screening strategies, which were classified by initial screening age (30, 35, 40, 45 and 50), and screening intervals (intervals at single time point, 1, 2, 5, 10, 20 years). The main model outputs were incremental cost-effectiveness ratios (ICERs), additional national healthcare expenditure and five-year LC death mortality. Results The ICERs for LDCT screening strategies vs non-screening strategy ranged from $16,086 per QALY to $3,675,491 per QALY in the male cohort, and from $36,624 per QALY to $5,943,556 per QALY in the female cohort. The annual increment national healthcare expenditures related to LDCT screening were ranged from $0.25 to $13.39 billion, which was lower in the cohort with older screening ages and lower screening frequencies. More repeated screening with LDCT was associated with a greater reduction in LC death: an annual LDCT screening was linked to an estimated reduction in five-year LC death by 27.27%-29.07%, while a one-off screening was linked to a reduction by 5.56%-5.83%. Conclusion Under a willingness-to-pay (WTP) threshold of three times the Chinese gross domestic product (GDP) per capita (US $37,654), annual screening with an initial screening age of 50 was the most cost-effective screening strategy in both the male and female cohorts. To take into account both the national healthcare expenditures and the effect of LDCT screening, results from this study support the implementation of LDCT screening annually for the general population aged 50.